Pembelajaran Kooperatif Tipe Numbered Head Together dan Think Pair Share ditinjau dari Motivasi - Laxmi Zahara; Khaerus Syahidi; Fartina Fartina; Baiq Aryani Novianti; Suriani Suriani (Kappa Journal, 2021)
This study aims to determine the effect of the NHT and TPS learning models on student achievement, the effect of motivation on student achievement, and the interaction between learning models and motivation on student achievement. This type of research is experimental research. The population in this study were all students of class VII MTs. NW Wanasaba totaling 60 people consisting of 3 classes, namely: class VIIA, VIIB and VIIC. The research sample was class VIIA and VIIB which was obtained by means of Cluster Random Sampling. The data collection technique was carried out using multiple choice objective test method. The prerequisite test used is the normality test and homogeneous test, where the normality test uses the chi-square test and the homogeneity test uses the Bartlet test. While the data analysis technique used to test the hypothesis is the Two Way ANOVA test and the Scheff test for further ANOVA testing. The results of the analysis in this study indicate that there is an influence of the NHT and TPS learning models on student achievement, there is an influence of motivation on student achievement, and there is no interaction between learning models and motivation on student achievement.